Public contracts in holding companies operating in the construction industry – a case of the Czech Republic - Brychta, Karel (Business: Theory and Practice, 2021)
This paper is produced as an exploratory study with the aim of carrying out a taxonomy of construction companies operating in the Czech Republic, taking into account the type and number of concluded public procurement contracts. In processing the multidimensional matrix describing the companies, a cluster analysis was used to identify the dependence between the set of variables. Results of the analysis suggest that the prevailing types of public procurement procedures include negotiated procedure without prior publications, open procedure and simplified below-threshold procedure, while from the point of view of the contracted value, the open procedure is of the highest importance. As for the cluster analysis conducted for the types of public procurement analysis, one can conclude that there is a relation between the number of public contracts concluded and the scope of the types. On the other hand, the extension of the conducted cluster analysis did not provide any conclusive evidence regarding the relationship between the types of public procurement contracts and the types of holding structures. Such a study has not been realised in the Czech Republic yet. Thus, the results of this study provide a background for research in the area of public procurement in the Czech Republic. Some potential research questions have been stated in the discussion part of the paper.